Green HR practices and environmental performance: The mediating mechanism of employee outcomes and moderating role of environmental values - Adeel, Muhammad; Mahmood, Shahid; Khan, Kanwal Iqbal; Saleem, Saima (Frontiers in Environmental Science, 2022)
Scholars focused on behavioral changes in employees rather than depending solely on technology enhancements due to institutions' poor and inefficient environmental performance. The purpose of this study is to observe the influence of green HR practices on work engagement and job satisfaction towards the environment and its effect on environmental performance of the universities. Further, the mediating effect of work engagement, job satisfaction and moderating impact of environmental values is assessed. The data was collected from 337 officials and faculty members of universities of Pakistan through structured questionnaire. The SPSS process macros results reveal that green HR practices has a significant impact on environmental performance, job satisfaction and work engagement. The mediation results reveal that work engagement and job satisfaction acted as a mean by which green HR practices of universities can positively affect the environmental performance. The moderation results reveal that environmental vales strengthen the relationship between green HR practices and environmental performance. The study highlights the significance of Green HR practices for environmental performance and extends the literature by enlightening the role of employee outcomes and environmental values.